The ketogenic diet as a promising adjunctive therapy for glioma: a comprehensive review - Arman Hamzei; Sara Hallaji; Seyed Farzin Hosseini; Arman Keymoradzadeh (Journal of Current Oncology and Medical Sciences)
Gliomas are the most prevalent primary tumors of the brain and spinal cord. Regrettably, the prognosis, especially for high-grade gliomas, remains quite bleak. In recent decades, there's been a growing trend to replace or combine radiotherapy with chemotherapy, targeted therapy, and personalized treatment for different patients. For example, carboplatin and vincristine are considered standard treatments for some patients with unresectable pediatric low-grade gliomas. In recent years, ketogenic diet (KD) has emerged as a promising investigational therapy for CNS tumors, with researchers exploring its use in conjunction with existing treatment modalities. This review article delves into the mechanisms underlying KD's potential therapeutic effects on glioma and its efficacy, safety profile, and overall role in glioma treatment.